2005
DOI: 10.1182/blood-2005-01-0358
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profiling of C/EBP targets identifies Per2 as a gene implicated in myeloid leukemia

Abstract: CCAAT/enhancer-binding proteins (C/EBPs) are a family of transcription factors that regulate cell growth and differentiation in numerous cell types. To identify novel C/EBP-target genes, we performed transcriptional profiling using inducible NIH 3T3 cell lines expressing 1 of 4 members of the C/EBP family. Functional analysis revealed a previously unknown link between C/EBP proteins and circadian clock genes. Our microarray data showed that the expression levels of 2 core components of the circadian network, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 56 publications
6
132
0
3
Order By: Relevance
“…Results from a mouse model study have indicated that circadian gene CKIdelta plays a role in lymphocyte physiology [36]. Observations from a human study have also demonstrated that expression levels of the circadian gene PER2 were reduced in lymphoma cell lines and in acute myeloid leukemia (AML) patient samples [37].…”
Section: Possible Mechanisms: Clock-controlled Immune Functionmentioning
confidence: 93%
“…Results from a mouse model study have indicated that circadian gene CKIdelta plays a role in lymphocyte physiology [36]. Observations from a human study have also demonstrated that expression levels of the circadian gene PER2 were reduced in lymphoma cell lines and in acute myeloid leukemia (AML) patient samples [37].…”
Section: Possible Mechanisms: Clock-controlled Immune Functionmentioning
confidence: 93%
“…Thus, impaired expressions of the clock genes Per1, Per2, or Per3 have been reported in human cancers originating from breast, lung, endometrium, pancreas, or colon, as well as in human myeloid leukemia Gery et al 2005Gery et al , 2006Gery et al , 2007aYeh et al 2005;Shih et al 2006;Krugluger et al 2007). Promoter methylation defects may account for such impaired clock gene expression .…”
Section: Implications For Cancer Chronotherapeuticsmentioning
confidence: 99%
“…Plasmids of 1 mg pTag1 (empty vector), pTTF-1, and pHNF3b/ FoxA2 were transfected into BHPs cells using Lipofectamine 2000 (Invitrogen). The zinc-inducible pMT-C/EBPb expression plasmid (Gery et al, 2005) was transfected into BHP cells (sublines 2 -7 and 7 -13), which were selected with 500 mg ml À1 G418 for 48 h.…”
Section: Plasmid Transfection and Colony Assaymentioning
confidence: 99%